2021
DOI: 10.1155/2021/6628142
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Hyperbaric Oxygen Therapy in Refractory Crohn’s Disease: An Observational Study

Abstract: Background and Aims. Patients may experience complications of Crohn’s disease (CD) even when treated with optimal medical therapy strategies. Previous data have shown the efficacy of hyperbaric oxygen therapy (HBOT) in the management of complicated CD. However, there is no consensus regarding the optimal number of sessions or duration of treatment regimens. The aim of the present study was to investigate the efficacy of HBOT in CD patients who were refractory to conventional medical management. Methods. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…The study included 20 patients 29]. Retrospective studies in patients with perianal fistulizing Crohn's disease, enterocutaneous fistulas, or pyoderma gangrenosum who underwent HBOT showed complete healing in 82.5% of patients with fistulas and 100% healing in patients with pyoderma gangrenosum [30]. In another study of 14 patients with refractory enterocutaneous fistulas, perineal disease, or pyoderma gangrenosum, 11 patients had improvement, healing, and local control of inflammation after HBOT sessions [31].…”
Section: Hyperbaric Oxygen Therapy's Role In Management Of Crohn's Di...mentioning
confidence: 99%
“…The study included 20 patients 29]. Retrospective studies in patients with perianal fistulizing Crohn's disease, enterocutaneous fistulas, or pyoderma gangrenosum who underwent HBOT showed complete healing in 82.5% of patients with fistulas and 100% healing in patients with pyoderma gangrenosum [30]. In another study of 14 patients with refractory enterocutaneous fistulas, perineal disease, or pyoderma gangrenosum, 11 patients had improvement, healing, and local control of inflammation after HBOT sessions [31].…”
Section: Hyperbaric Oxygen Therapy's Role In Management Of Crohn's Di...mentioning
confidence: 99%
“…These included 4 CRs, 11 CS, and 1 case-controlled trial with a total of 164 patients. 23,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] The majority of patients had underlying severe disease refractory to conventional therapy, including corticosteroids, antibiotics, immunomodulators (IMs), surgery, and/or biologic agents. Treatment outcomes were reported based on clinical judgment, magnetic resonance imaging (MRI), standardized questionnaires, and/or endoscopy.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“…Six studies were published in the prebiologic era (before 1998) 23,42,43,[46][47][48] and 10 studies were published in the prebiologic era. 41,44,45,[49][50][51][52][53][54][55] Subgroup analysis based on the timing of publication demonstrated that the pooled overall clinical response to HBOT was 86% (95% CI: 0.68-0.95, I 2 = 0) in the prebiologic era and 82% (95% CI: 0.74-0.87, I 2 = 0) in the biologic era (Fig. 4A).…”
Section: Effectiveness Of Hyperbaric Oxygen Therapy In Fistulizing Cr...mentioning
confidence: 99%
See 1 more Smart Citation
“…HBOT was identified as an adjunctive therapy for treating IBD, but not considered as the main treatment, as the results from various studies varied and bias was observed. In a study 48 focusing on the effect of HBOT on complicated Crohn’s disease (in the patients who were refractory to conventional treatment practices), it was identified that HBOT was effective on patients with various complications including perianal fistulizing Crohn’s disease (pCD) (80% healing rate), enterocutaneous fistulas (ECF) (84.6%), or pyoderma gangrenosum (PG) (100%). Similarly, HBOT was also identified to be an effective adjunctive approach for treating metastatic Crohn’s disease.…”
Section: Hbot For Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%